2011
DOI: 10.1007/s10570-011-9613-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of multi-functionalized cotton fabrics treated by extracts of gromwell and gallnut

Abstract: Extracts from the root of Lithospermum erythrorhizon (gromwell) have been used for many centuries as a natural red dye and crude drugs with excellent performance for wound healing. In particular, shikonin a major constituent of the gromwell colorant is reported to possess antibacterial, antioxidant, anti-inflammatory, antitumor activities, etc. Therefore, we tried to manufacture antimicrobial and antioxidant cotton fabrics for biocompatible clothing materials using the natural stuff and environmentally friendl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 25 publications
0
27
0
1
Order By: Relevance
“…20 Even though pyrogallol also has antiseptic properties, the carboxyl groups in gallic acid derivatives are expected to be an important site to form esterification with hydroxyls in cotton cellulose. 11 Therefore, we suggested that in order to obtain a gallnut extract having a higher concentration of gallic acid derivatives, a lower temperature was recommendable for gallnut extraction.…”
Section: Elemental Analysis Of Gallnut Extractmentioning
confidence: 99%
See 3 more Smart Citations
“…20 Even though pyrogallol also has antiseptic properties, the carboxyl groups in gallic acid derivatives are expected to be an important site to form esterification with hydroxyls in cotton cellulose. 11 Therefore, we suggested that in order to obtain a gallnut extract having a higher concentration of gallic acid derivatives, a lower temperature was recommendable for gallnut extraction.…”
Section: Elemental Analysis Of Gallnut Extractmentioning
confidence: 99%
“…Thus, the phenolic compounds were possibly incorporated into the cotton fabrics by esterification between the cellulose hydroxyl of the cotton fibers and carboxyl of the gallic acid and ellagic acid. 11 However, the ester C-O stretching peak was not identified from the FTIR spectrum because it overlapped the other C-O-C stretching peak of cellulose ranging from 1000 to 1300 cm À1 . 26 The spectrum change was identically observed in the cotton fabrics treated by the pad-dry-cure process as well (Figure 3(f)).…”
Section: Surface Properties Of Gallnut Extract Treated Cotton Fabricsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, there are a lot of studies in which Quercus Aegilops (Figure1) extract used as bio mordant in this study was used as mordant and features such as colour, fastness, being antibacterial and antimicrobial were examined [11][12][13][14][15].…”
mentioning
confidence: 99%